Predictor Of Intention In Purchasing Halal Skin Care Products Among User And Non-user - Azreen Jihan Che Mohd Hashim; Nur Shuhada Kamarudin; Junaidah Abu Seman; Muhamad Azrin Nazri; Nur Qamarina Sharom; Rosidah Musa (Zes Rokman Resources, 2024)
Non-Indexed Publication